Regulation of LIM-kinase 1 and cofilin in thrombin-stimulated platelets - Pandey, Dharmendra (The American Society of Hematology, 2006)
Cofilin is a regulator of actin filament dynamics. We studied whether during platelet activation Rho kinase stimulates LIM kinase (LIMK) leading to subsequent phosphorylation and inactivation of cofilin. Platelet shape change and aggregation/secretion were induced by low and high concentrations of thrombin, respectively. We found that during these platelet responses Rho kinase activation was responsible for mediating rapid Thr508 phosphorylation and activation of LIMK-1 and for the F-actin increase during shape change and, in part, during secretion. Surprisingly, during shape change cofilin phosphorylation was unaltered, and during aggregation/secretion cofilin was first rapidly dephosphorylated by an okadaic acid–insensitive phosphatase and then slowly rephosphorylated by LIMK-1. LIMK-1 phosphorylation and cofilin dephosphorylation and rephosphorylation during aggregation were independent of integrin α(IIb)β(3) engagement. Cofilin phosphorylation did not regulate cofilin association with F-actin and was unrelated to the F-actin increase in thrombin-activated platelets. Our study identifies LIMK-1 as being activated by Rho kinase in thrombin-stimulated platelets. Two counteracting pathways, a cofilin phosphatase and LIMK-1, are activated during platelet aggregation/secretion regulating cofilin phosphorylation sequentially and independently of integrin α(IIb)β(3) engagement. Rho kinase–mediated F-actin increase during platelet shape change and secretion involves a mechanism other than LIMK-1–mediated cofilin phosphorylation, raising the possibility of another LIMK substrate regulating platelet actin assembly.